Reflection of the European Mythologies in J. R. R. Tolkien's The Silmarillion - Petr, Zdeněk (Univerzita Pardubice, 2013)
This paper deals with the analysis of certain elements of the European mythologies, which are reflected in J. R. R. Tolkien's The Silmarillion. The definition of specific terms concerning mythologies and the contextualization of J. R. R. Tolkien and his works are followed by the actual analysis in the second half of the paper.
Odraz evropských mytologií v Silmarillionu od J. R. R. Tolkiena
Keywords: Tolkien, J. R. R.; Silmarillion; mythology; influence; mytologie; vliv